Calibration of the superconducting gravimeter CT#043 with an absolute gravimeter FG5#210 at Syowa Station, Antarctica - Fukuda, Yoichi; Iwano, Sachiko; Ikeda, Hiroshi; Hiraoka, Yoshifumi; Doi, Koichiro (National Institute of Polar Research, 2005)
P(論文) For the purpose of calibration of the superconducting gravimeter (SG) model CT#043 at Syowa Station, Antarctica, we carried out parallel observations with the absolute gravimeter (AG) FG5#210. Although the AG measurements were conducted from December 31, 2003 to February 9, 2004, SG measurements before January 17 are found to have suffered artificial sensitivity change. We finally adopted data from January 17 to February 1, 2004, and obtained the scale factor of CT#043 as -59.461 ±0.079μGal/volt by linear regression analysis. The result achieved a relative accuracy of around 0.1%, which is important to modern precise tidal analysis. We also determined the scale factor by comparing the data of parallel observations with the SG TT70#016. Both values showed good agreement, supporting the reliability of the above mentioned value. departmental bulletin paper